1993
DOI: 10.1071/ar9931667
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture and temperature affect condensed tannin concentrations and growth in Lotus corniculatus and Lotus pedunculatus

Abstract: Maku big trefoil and Dewey birdsfoot trefoil were grown at 14/10, 20/16, 26/22 and 32/28�C (14/10 h) in growth cabinets. Growth rates and condensed tannin (CT) concentrations were measured as soil moisture was changed from field capacity (FC) to 20% FC to FC again in three regrowth cycles. Seasonal dry matter accumulation and CT concentrations were also measured on these cultivars together with Sharnee big trefoil, Monarch cicer milkvetch, Chemung crownvetch and WL605 lucerne at two sites in the field. Condens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 0 publications
4
24
0
1
Order By: Relevance
“…(1994) reported that Lotus pedunculatus had more CT when grown at 30°C than 20°C. Similarly, Anuraga et al. (1993) observed higher CT levels in Lotus pedunculatus but not in Lotus corniculatus at 30°C.…”
Section: Discussionmentioning
confidence: 66%
“…(1994) reported that Lotus pedunculatus had more CT when grown at 30°C than 20°C. Similarly, Anuraga et al. (1993) observed higher CT levels in Lotus pedunculatus but not in Lotus corniculatus at 30°C.…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, both condensed tannin concentration and plant re-growth at 30°C were severely reduced after the plants were cut back, which could indicate low levels of storage carbohydrates in the roots prior to harvesting. In a study by Anuraga et al, 14 low temperatures have been reported to elevate condensed tannin concentrations in L corniculatus whilst high temperature and drought stress increased condensed tannin levels in L uliginosus indicating species differences in condensed tannin biosynthesis in response to temperature.Briggs and Schultz 31 observed that, contrary to expectation, investment in condensed tannin accumulation was not at the expense of plant growth, but was positively correlated with shoot size. In the current work, plants of genotype S41 had higher condensed tannin concentrations relative to S33 and S50, but their growth rate and daily biomass production were comparable.…”
Section: Discussionmentioning
confidence: 94%
“…Some reports on the effects of temperature and drought on condensed tannin accumulation in Lotus corniculatus have been published 14,15 but the effects of elevated CO 2 or a combination of environmental variables have not been reported. Furthermore, no information is currently available on the relationship between environmental growth conditions and condensed tannin accumulation and subsequent effects on tissue digestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If concentrations could be maintained at the top of this range there may be advantages for ruminant nutrition and bloat prevention, so the reasons for variability need to be determined. A range of biotic and abiotic factors (soil moisture and fertility, light intensity, animal grazing) can influence CT concentrations (Briggs 1990;Anuraga et al 1993;Gebrehiwot et al 2002), with varying responses amongst plant species. In this study, CT concentration was affected by the stage of flower development, being highest when flowers were in full bloom, and low in green buds or senescent flowers.…”
Section: Condensed Tanninsmentioning
confidence: 99%